2011
DOI: 10.1007/s10433-011-0203-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of proactive behaviour with job-related affective well-being and anticipated retirement age: an exploration among older employees in Belgium

Abstract: Developed countries throughout the world are challenged with the ageing of their labour force. In these societal contexts, low employment rates and early labour market exits of older employees are at stake, as well as arrangements for retirement, financial household considerations and mutual obligations between generations. Although proactive behaviour has been extensively studied, no research has addressed the proactive behaviour of older employees themselves when facing (re)hiring and retention versus early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
9
1
Order By: Relevance
“…Experimental studies have confirmed that positive emotions "broaden the scope of attention and thoughtaction repertoires" (Fredrickson and Branigan, 2005, p 313). Broaden hypothesis was also confirmed in the work contextresearch shown that positive emotions are related to proactive behaviors at work (Fritz and Sonnentag, 2007;Claes and van Loo, 2011). Building on broaden hypothesis (Fredrickson, 2001), we argue that because positive emotions at work broaden habitual modes of thinking and acting, they also predict job crafting behaviors.…”
Section: Positive Emotions and Job Craftingsupporting
confidence: 57%
See 1 more Smart Citation
“…Experimental studies have confirmed that positive emotions "broaden the scope of attention and thoughtaction repertoires" (Fredrickson and Branigan, 2005, p 313). Broaden hypothesis was also confirmed in the work contextresearch shown that positive emotions are related to proactive behaviors at work (Fritz and Sonnentag, 2007;Claes and van Loo, 2011). Building on broaden hypothesis (Fredrickson, 2001), we argue that because positive emotions at work broaden habitual modes of thinking and acting, they also predict job crafting behaviors.…”
Section: Positive Emotions and Job Craftingsupporting
confidence: 57%
“…However, the B&B theory describes the general mechanism of positive emotions, not related to any domain of human functioning. Empirical evidence for this hypothesis in the context of proactive behaviors is scarce (Fritz and Sonnentag, 2007;Claes and van Loo, 2011). No previous longitudinal studies have also investigated the role of positive emotions at work and collective flow at work as predictors of job crafting dimensions.…”
Section: Study Contributionmentioning
confidence: 99%
“…5 (H 5 ) introduces the control variables of Financial Management Practices according to Zaniboni et al (2010) -Education, type of employment, job tenure, length of their job, by considering aging's role (Zaniboni, 2015) in the financial decision-making towards retirement according to the framework. Variables linked to the people's job environment affect to design retirement strategies and they usually have effect on previous financial practices in retirement time (Claes & Van Loo, 2011;Davies et al, 2017). Other control variable on financial practices is the large levels of education associated to better financial practices for retirement saving behaviour (Koposko et al, 2016).…”
Section: Model and Methodsmentioning
confidence: 99%
“…This may increase both their perceived internal and external employability (Kossek, Roberts, Fisher and Demarr 1998;Sturges et al 2002;Zacher and Frese 2011). Moreover, in the specific case of the late career, older workers who demonstrate a self-directed career attitude may counter employers' stereotypical belief of them being reluctant to change and focused on withdrawal or decline (Claes and van Loo 2011) and consequently strengthen their perceived employability. We therefore formulate the following hypotheses:…”
Section: Self-directedness Relates To Perceived Employabilitymentioning
confidence: 99%
“…In Belgium, the legal retirement age is set at age 65. Furthermore, employee retirement is usually studied among individuals in late career, that is among workers aged 50 or older (see for instance Chan and Stevens 1999;Claes and Van Loo 2011;Herrbach, Mignonac, Vandenberghe and Negrini 2009). Therefore, this study uses the observations from the 285 employed respondents aged 50 to 64 years old with no missing values for the studied variables.…”
Section: Procedures and Samplementioning
confidence: 99%